AKTIFITAS BIOREPRODUKSI GENERATIF DAN KEMUNGKINAN OTOFERTILISASI PADA BUNGA BEBERAPA JENIS ZINGIBERACEAE MINOR LIAR - Rachman, Erlin (BERITA BIOLOGI, 1998)
ApreBminary study on flowers of some wild-minor Zingiberaceae species was conducted to know their generative reproduction andpossiblefertilisation mechanism. Nine species from five wild-minor Zingiberaceae genera grown in Bengkulu Forestry Grand Park :Achasma macrocheilos Griff., A.triorgyale Bak.,Amomum aculeatum Roxb.,A.maxima Roxb.,A.testaceum BJdl, Homstedtia minor VaL, H. scyphus Ret.Nicolaia speciosa Bl, and Zingiber aromaticum VaL, were in situ observed. As much as 90% of the species were found in flowering stage in the study periods, between September and December 1995, 75% of the plants set fruit and seed while 25% set seeded fruit according to native people from neighbour village. All of the flowers showed that many spikelet might be anthesi edper spike per day and were terminally heated on non leafy "stem".Some stigmas observed were occupied by some pollens though pollinator was absent. In addition, stigma - anther distances were very near (0-3 mm).We found that generative bioreproduction was active and productive and autofertili^ation mechanism might be considered to be occurred on the species.